2020
DOI: 10.1371/journal.pone.0232878
|View full text |Cite
|
Sign up to set email alerts
|

Remote monitoring of clubfoot treatment with digital photographs in low resource settings: Is it accurate?

Abstract: Background Clinical examination and functional assessment are often the first steps to assess outcome of clubfoot treatment. Clinical photographs may be an adjunct used to assess treatment outcomes in lower resourced settings where physical review by a specialist is limited. We aimed to evaluate the diagnostic performance of photographic images of patients with clubfoot in assessing outcome following treatment. Methods In this single-centre diagnostic accuracy study, we included all children with clubfoot from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, telemedicine-oriented patient education may well solve the problem [37,61,62]. Studies conducted for virtual consultations for orthopedics usually focus on new solutions and technologies [59,[63][64][65][66][67][68][69], patient and clinician satisfaction [4,24,26,46,49,[70][71][72][73][74][75][76][77], clinical outcome measures [78][79][80][81][82], and cost analysis of traditional versus teleconsultation [82][83][84][85][86][87].…”
Section: Discussionmentioning
confidence: 99%
“…However, telemedicine-oriented patient education may well solve the problem [37,61,62]. Studies conducted for virtual consultations for orthopedics usually focus on new solutions and technologies [59,[63][64][65][66][67][68][69], patient and clinician satisfaction [4,24,26,46,49,[70][71][72][73][74][75][76][77], clinical outcome measures [78][79][80][81][82], and cost analysis of traditional versus teleconsultation [82][83][84][85][86][87].…”
Section: Discussionmentioning
confidence: 99%
“…Another opportunity is that the data can be shared remotely with experts and study groups for treatment monitoring. An interesting study has been done by Smythe et al 111 They have shown that remote monitoring for the assessment of clubfoot treatment using photographs has massive potential in low-resource settings. However, there is a need to define protocols for data acquisition to increase the effectiveness of such technologies.…”
Section: Treatment Challenges: Contemporary Engineeringmentioning
confidence: 99%
“…It require extensive orthopedic care. The muscular and bone level tendinous structures are representative of the idiopathic foot disease [3][4] . The midfoot cavus, hindfoot varus, and a hindfoot equinus are commonly observed in the idiopathic-club foot.…”
Section: Introductionmentioning
confidence: 99%